Impact of cocoa fibers on the stability and rheological properties of chocolate ganaches. (March 2021) - Merachli, Fadi; Devienne, Julia; Delmas, Romain; Plawinski, Laurent; Leal-Calderon, Fernando; Delample, Mathieu
Abstract: This work investigates the structure and behavior of model oil-in-water chocolate ganaches by comparing two systems differing in the nature of the dispersed (fat) phase: cocoa butter and cocoa mass (mix of cocoa butter and fibers). Significant differences regarding the textural properties and stability were evidenced. Concentrated liquid emulsions made with cocoa butter had a thick and homogeneous macroscopic aspect. Upon cooling, fat crystallization produced partial coalescence and the emulsions became solid. With molten cocoa mass, a homogeneous aspect was observed until 50 g/100 g of dispersed phase and a grainy texture was obtained at larger fractions. This textural transition was interpreted as being due to a jamming transition. Both conventional and fluorescence microscopy revealed that cocoa fibers were transferred from the fat phase to the aqueous phase and were partially anchored to the interfaces. Upon cooling, cocoa fibers acted as a physical barrier that limited the extent of partial coalescence. Highlights: Oil-in-water ganaches based on cocoa butter and whole cocoa mass were formulated. Their rheological behavior was different for the same dispersed fraction. Cocoa fibers were transferred into the aqueous phase. Cocoa fibers limited the extent of partial coalescence upon fat recrystallization. Cocoa fibers produced a jamming transition at high chocolate content.